The Influence of Motivation and Compensation on Performance Employees : Case Study from Social Service of the City of Makassar, Indonesia - Taufan A, Rezky Ratnasari (Manunggal Halim Jaya, 2024)
This study aims to determine the effect of motivation and compensation on employee performance at the Makassar City Social Service. This study uses questionnaire data sourced from Makassar City Social Service Employees The method used in this research is multiple regression analysis method using a questionnaire. The population in this study were employees of the Makassar City Social Service and the sample in this study were 79 employees of the Makassar City Social Service selected through the saturated sample method. The results of this study indicate that based on partial tests motivation and compensation have a positive and significant effect on employee performance and based on simultaneous tests motivation and compensation have a positive and significant effect on employee performance.